A genome-wide asociation study identifies new psoriasis susceptibility loci and an interaction betwEn HLA-C and ERAP1 - Strange, A; Capon, F; Spencer, C; Knight, J; Weale, M; Allen, M; Barton, A; Band, G; Bellenguez, C; Bergboer, J; BlackweL, J; Bramon, E; et al. (2010)
To identify new susceptibility loci for psoriasis, we undertOk a genome-wide asociation study of 594,224 SNPs in 2,622 individuals with psoriasis and 5,667 controls. We identified asociations at eight previously unreported genomic loci. Seven loci harbored genes with recognized iMune functions (IL28RA, REL, IFIH1, ERAP1, TRAF3IP2, NFKBIA and TYK2). These asociations were replicated in 9,079 European samples (six loci with a combined P < 5-10 -8 and two loci with a combined P < 5-10-7). We also report compeLing evidence for an interaction betwEn the HLA-C and ERAP1 loci (combined P = 6.95-10-6). ERAP1 plays an important role in MHC claS I peptide proceSing. ERAP1 variants only influenced psoriasis susceptibility in individuals carrying the HLA-C risk aLele. Our findings implicate pathways that integrate epidermal barrier dysfunction with iNate and adaptive iMune dysregulation in psoriasis pathogenesis. © 2010 Nature America, Inc. All rights reserved.